2019
DOI: 10.9734/ajrimps/2019/v6i130093
|View full text |Cite
|
Sign up to set email alerts
|

Laxative Effects of Aqueous Extract of Sida acuta Leaves in Loperamide- Induced Constipation in Wistar Rats

Abstract: Aim:To investigate the laxative potentials of aqueous leaf extract of Sida acuta in loperamideinduced constipation in Wistar rats. Methods: Constipation was induced by oral administration of loperamide (3 mg/kg b.wt.). The Nweje et al.; AJRIMPS, 6(1): 1-7, 2019; Article no.AJRIMPS.47572 2 constipated rats were orally treated daily either with 200, 400, 800 mg/kg body weight per day of the extract or 0.21 mg/kg bisacodyl (reference drug) for 7 days while the normal and constipated control groups received dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Changes in fecal pellet number, weight, and water content in rats with loperamide-induced constipation are important factors that need to be improved while aiming to relieve constipation. Previous studies have reported a marked reduction in the fecal pellet count, weight, and water content, in rats treated with loperamide [ 22 , 23 ], whereas prebiotic intake is known to improve the fecal parameters [ 24 , 25 ]. The MOS used in this study also improved the fecal pellet number and water content (Figures 2 and 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in fecal pellet number, weight, and water content in rats with loperamide-induced constipation are important factors that need to be improved while aiming to relieve constipation. Previous studies have reported a marked reduction in the fecal pellet count, weight, and water content, in rats treated with loperamide [ 22 , 23 ], whereas prebiotic intake is known to improve the fecal parameters [ 24 , 25 ]. The MOS used in this study also improved the fecal pellet number and water content (Figures 2 and 3 ).…”
Section: Discussionmentioning
confidence: 99%